Settlement of Rights Disputes Due to Unilateral Wage Reductions during the Covid 19 Pandemic - Besty Habeahan (LEGAL BRIEF, 2022)
Because of There is a working relationship between employers and workers, so they have rights and obligation that the workers receive namely wages/salary. The covid 19 pandemic has impact on decreasing economic activity, so it cause the company lost out. To maintain the continuity of the business, the employers reduce the wages of workers unilaterally and for the action the employers violate worker's rights and losses. Therefore, the problem of study is whether permissible to reduce workers wages during the covid 19 pandemic and how is the process to solve the disputes over the right to reduce worker's wages unilaterally by company during the covid 19 pandemic. The research method used is normative juridical,namely using data sources based on positif law. The results of the research are based on Kepnaker No.104 2021 that wages for workers that work from home (WFH) , WFH are still paid. If it turns out that company is unable to pay, wage reductions can be made and the amount based on worker's agreement. The problem solving of reducing wages unilaterally by the employers is carried out in UU No.2 of 2004 concern to the settlement of Industrial Relations Disputes, namely bipartite or meditation,and if the bipartite or meditation fails, it can be resolved through the industrial relation court of first instance, and its possible to submit legal remedies directly to the supreme Court.